Augustine's intellectual conversion the journey from Platonism to Christianity - Dobell, Brian (Cambridge ; New York : Cambridge University Press, 2009)
"This book examines Augustine's intellectual conversion from Platonism to Christianity, as described at Confessions 7.9.13-21.27. It is widely assumed that this occurred in the summer of 386, shortly before Augustine's volitional conversion in the garden at Milan. Brian Dobell argues, however, that Augustine's intellectual conversion did not occur until the mid 390s, and develops this claim by comparing Confessions 7.9.13-21.27 with a number of important passages and themes from Augustine's early writings. He thus invites the reader to consider anew the problem of Augustine's conversion in 386: was it to Platonism or Christianity? His original and important study will be of interest to a wide range of readers in the history of philosophy and the history of theology."--P. preceeding t.p.
Augustine's conversion to Christianity -- The way of authority -- The development of Augustine's Christology -- The way of reason -- The problem of evil and the development of Augustine's metaphysics -- The graded ascent -- The rejection of Platonic ascent -- The Ostia ascent -- Augustine the Porphyrian.
Includes bibliographical references (p. 239-245) and index.
Description based on print version record.
Keywords: Augustine, -- Saint, Bishop of Hippo -- Criticism and interpretation; Augustine, -- Saint, Bishop of Hippo; Conversion -- Christianity; RELIGION -- Christian Church -- History; RELIGION -- Christianity -- History; Augustinus, Aurelius; Konversion (Religion); Electronic books